Addition of elotuzumab to lenalidomide and dexamethasone for patients with newly diagnosed, transplantation ineligible multiple myeloma (ELOQUENT-1): an open-label, multicentre, randomised, phase 3 trial - Dimopoulos, Meletios A.; Richardson, Paul G; Bahlis, Nizar J; Grosicki, Sebastian; Cavo, Michele; Beksaç, Meral; Legieć, Wojciech; Liberati, Anna M; Goldschmidt, Hartmut; Belch, Andrew; Magen, Hila; Larocca, Alessandra; et al. (The lancet. Haematology, 2022)
Background - Elotuzumab plus lenalidomide and dexamethasone has shown improved progression-free and overall survival versus lenalidomide and dexamethasone in patients with relapsed or refractory multiple myeloma. We aimed to assess these regimens in patients with newly diagnosed multiple myeloma who are ineligible for haematopoietic stem-cell transplantation (HSCT). - Methods - ELOQUENT-1 is an open-label, multicentre, randomised, phase 3 trial conducted at 185 hospitals, oncology practices, and research centres in 19 countries. Eligible patients were aged 18 years or older with newly diagnosed, untreated, symptomatic myeloma and not candidates for high-dose therapy plus HSCT, and an Eastern Cooperative Oncology Group (ECOG) performance status of 2 or lower. Patients were randomly assigned (1:1) to receive elotuzumab plus lenalidomide and dexamethasone or lenalidomide and dexamethasone using an interactive voice response system, stratified by the International Staging System (ISS; stage I-II vs III), age (<75 years vs ≥75 years), and ECOG performance status (0 vs 1-2). Patients in the elotuzumab plus lenalidomide and dexamethasone group received elotuzumab administered intravenously at 10 mg/kg on days 1, 8, 15, and 22 during cycles 1 and 2, days 1 and 15 during cycles 3-18, and then at 20 mg/kg on day 1 for subsequent cycles. In both treatment groups, patients received 25 mg lenalidomide orally on days 1-21 of each cycle and 40 mg dexamethasone on days 1, 8, 15, and 22 of each cycle. The primary endpoint was progression-free survival, as per the primary definition from European Society for Blood and Marrow Transplantation criteria in all randomly assigned patients (intention-to-treat population). This study is registered with ClinicalTrials.gov, NCT01335399 (completed). - Findings - Between Aug 4, 2011, and June 19, 2014, 748 patients were randomly assigned (374 in each treatment group) and 742 patients received treatment (333 (90%) of 371 in the elotuzumab plus lenalidomide and dexamethasone group vs 339 (91%) of 371 in the lenalidomide and dexamethasone group discontinued treatment). The median age of patients was 73·0 years (IQR 69·0-78·0), 294 (39%) patients were 75 years or older. Most patients were White (711 [95%]) and male (412 [55%]). At a minimum follow-up of 65·3 months, the median progression-free survival was not significantly different between the groups: 31·4 months (95% CI 26·2-36·8) in the elotuzumab plus lenalidomide and dexamethasone group versus 29·5 months (23·5-34·3) in the lenalidomide and dexamethasone group (HR 0·93, 95·71% CI 0·77-1·12; stratified log-rank p=0·44). The median follow-up was 70·6 months (IQR 35·1-79·2). The most common grade 3-4 treatment-related adverse event was neutropenia (64 [17%] of 371 vs 79 [21%] of 371). Study drug toxicity was the reported cause of death in five (1%) versus four (1%) patients. - Interpretation - Elotuzumab plus lenalidomide and dexamethasone did not significantly improve progression-free survival versus lenalidomide and dexamethasone in patients with newly diagnosed multiple myeloma who are ineligible for HSCT. Although these data contribute to the treatment landscape, further research is needed to find ways to improve treatments in the front-line setting. - Funding - Bristol Myers Squibb.
Gesehen am 01.02.2023